The Role Of Waitresses In Serving Breakfast During The Covid-19 Pandemic At Intercontinental Bali - Dimas Bima Andika; Faozen Faozen (Empat Sembilan Publisher, 2024)
This article provides an overview of the restaurant options and the role of waitresses at the Intercontinental Bali Resort during the COVID-19 pandemic. The resort has a variety of restaurants such as Taman Gita, Sunset Beach Bar & Grill, Bella Cucina, Jimbaran Gardens, and KO Japanese, which serve international and local dishes. The waitress at this resort has an important role in ensuring optimal service, especially at breakfast. Their roles include preparing the area, implementing health protocols, hygiene, coordinating with the kitchen, and serving guests in a friendly manner. During the pandemic, strict health protocols were implemented to protect guests and staff, such as the use of masks, face shields, and hand sanitizers. In addition, waitresses must also ensure social distancing and manage time so that there are no long queues. After breakfast, the waitress cleans and prepares for the next session. Regular evaluations and briefings are carried out to improve the quality of service. The results of this research are expected to provide deeper insights and help the hospitality industry adapt and improve service quality in the future